PERSIAPAN PERSALINAN NORMAL DENGAN MELAKUKAN SENAM HAMIL PADA IBU HAMIL TRIMESTER III DI DESA JAMBE SARI KABUPATEN BANYUWANGI - Miftahul Hakiki; Nurul Eko Widiyastuti (LPPM Universitas dr. Soebandi, 2023)
Pregnancy is a physiological change experienced by the mother during her pregnancy. And the care given to pregnant women must be care that can minimize intervention (Andarwulan, et al., 2021). Pregnancy exercise is a fitness program that is intended for pregnant mother. Therefore, pregnancy exercise has the principle of special movements that are adapted to the condition of pregnant women. Exercises in pregnancy gymnastics are specifically designed to make pregnant women healthy and fit, reduce complaints that arise during pregnancy and prepare physically and psychologically for mothers to face childbirth (Manuaba, et al., 2013). The purpose of the pregnancy exercise program is to help pregnant women feel comfortable, safe from the time the baby is in the womb until birth. Pregnancy exercise is a relaxation exercise carried out by mothers who are pregnant from 23 weeks until the time of birth and pregnancy exercise is one of the activities in services during pregnancy (prenatal care). So it is hoped that pregnant women during their pregnancy can do pregnancy exercises starting at 23 weeks of age so that the delivery process can be normal. The implementation of this activity was carried out on third trimester pregnant women in Jambe Sari Village in a gradual period of time. The results obtained were the enthusiasm of the third trimester pregnant women who came during pregnancy exercise.